Inhibitors of Continuous Professional Development of Business Studies Teachers in Junior Secondary Schools in Anambra State - Nwosu, Ngozi Lorretta; Onwubuya, Uju Nkiru (International Journal of Educational Management, 2021)
The study determined inhibitors of continuous professional development of business studies teachers in junior secondary schools in Anambra State. Two research questions guided the study and two hypotheses were tested at 0.05 level of significance. Descriptive survey research design was adopted for the study. The study was carried out in Anambra State. The population of the study comprised 684 business studies teachers from the 258 public secondary schools in Anambra State. Through simple random sampling technique the researcher sampled 40% of the total population of 684 business studies teachers which amounted to 273 business studies teachers in public secondary schools in Anambra State. The instrument for data collection was a structured questionnaire developed by the researcher. The instrument was validated by three experts in education.The test of reliability through Cronbach Alpha technique yielded an overall coefficient value of 0.79. Mean and standard deviation were used to answer the research question while t-test was used to test the hypotheses. Findings revealed that the benefits of Continuous Professional Development (CPD) to business studies teachers are that it keeps teachers' abreast with the latest innovation in the teaching profession, keeps business studies teachers informed on the current trends in business and entrepreneurship, equips business studies teachers with skills among others. Findings also revealed that the inhibitors of CPD of business teachers in Anambra State include insufficient funds, lack of appropriate reward for professional growth and poor attitude of teachers and tight school schedule among others. Based on these findings, recommendations were made.